Family ties : a novel - Steel, Danielle (London : Corgi Books, 2011)
Annie Ferguson was a bright young Manhattan architect. Talented, beautiful, just starting out with her first job, new apartment and boyfriend, she had the world in the palm of her hand--until a single phone call altered the course of her life forever. Overnight, she became the mother to her sister's three orphaned children, keeping a promise she never regretted making, even if it meant putting her own life indefinitely on hold.
Keywords: Parenting -- Fiction; Domestic fiction